Pengaruh Kualitas Produk Kualitas Pelayanan Dan Fasilitas Terhadap Kepuasan Pelanggan : Studi Empiris Pondok Jahe Geprek Samsudin - Riki Yogi Yusnanto; Roby Setiadi; Dumadi Dumadi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aimms to examine the inflluence of product quality, service quality and facilities on customer satisfaction at Pondok Jahe Geprek Samsudin. In this a research, quantitative methods were used with a descriptive design. The sampling technique uses a purposive samplings. So, data was collected using a questionnaire distributed to customers who bought food or drinks at Pondok Jahe Geprek with a total of 75 respondents. This research instrument is a ratio scale and data analysis uses multiple linear regression. It was found that the product quality variable (X1) partially did not have a significant influence on customer satisfactions, with a calculated t value of 0.188 < 1.993 t table and a significance value of 0.852 > 0.05. Then the service quality variable (X2) partially has a significant effect on the customer satisfaction variable, with a calculated t value of 2.834 > 1.993 t table, and a significance value of 0.006 < 0.05. Then, the facility variable (X3) partially does not have a significant influence on customer satisfaction, with a calculated t value of 1.664 < 1.993 and a significance value of 0.101 > 0.05. Apart from that, simultaneously all x variables have an influence on the y variable with the calculated f value of 3.984 > 2.73 f table and a significance value of 0.018 < 0.05. The implication of these findings is that service quality has a significant influence on the level of partial customer satisfaction. Then product quality, service quality and facilities simultaneously have an impact or influence on the level of customer satisfaction. The conclusion of this a research is that the variables of products quality, service quality and facilities have been proven to simultaneously influence the level of customer satisfaction. Suggestions for future researchers are to increase the number of research samples and examine other variables it that have not being study and have the possibility of influencing the customer satisfaction variable.